2021
DOI: 10.33225/pec/21.79.657
|View full text |Cite
|
Sign up to set email alerts
|

Student Misbehaviour, Teacher Self-Efficacy, Burnout and Job Satisfaction: Evidence From Croatia

Abstract: Student misbehaviour is an increasing problem of contemporary school. The aim of this research was to examine the extent to which teachers perceive student misbehaviour, how self-efficient they are, how satisfied they feel with support from their environment and with the teaching job itself, and to which extent they experience the burnout syndrome. The research included 603 primary and secondary school teachers in the Republic of Croatia, and it found quite low, but significant negative correlations between st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
(53 reference statements)
1
2
0
3
Order By: Relevance
“…Research carried out so far in Croatian schools indicates relatively high perceptions of teacher self-efficacy and job satisfaction. These perceptions are lower when it comes to emotional exhaustions, depersonalisation and principal support (T. Vidić et al, 2021). With the aim of expanding the existing knowledge, in the research we examined to which extent demographic variables, principal support and teacher self-efficacy contribute to collective teacher efficacy.…”
Section: Collective Efficacymentioning
confidence: 99%
“…Research carried out so far in Croatian schools indicates relatively high perceptions of teacher self-efficacy and job satisfaction. These perceptions are lower when it comes to emotional exhaustions, depersonalisation and principal support (T. Vidić et al, 2021). With the aim of expanding the existing knowledge, in the research we examined to which extent demographic variables, principal support and teacher self-efficacy contribute to collective teacher efficacy.…”
Section: Collective Efficacymentioning
confidence: 99%
“…Stresli taleplere başarılı bir şekilde uyum sağlanması ise, mesleki tükenmişliğin ortaya çıkmasını engelleyecektir (Caprara vd., 2003;Skaalvik ve Skaalvik, 2007;Schwarzer ve Hallum, 2008). Şimdiye kadar alan yazında, tükenmişlik ve öz yeterliliği araştıran çok sayıda çalışma olmasına rağmen (Alarcon, Eschleman ve Bowling, 2009;Bümen, 2010;Skaalvik ve Skaalvik, 2010;Karahan ve Balat, 2011;Federici ve Skaalvik, 2012;Gündüz, 2012;Gömleksiz ve Serhatlıoğlu, 2013;Sarıcam, 2015;Shoji vd., 2016;Arslan, 2019;Makara-Studzińska, Wajda ve Lizińczyk, 2020;Vidić, Đuranović, ve Klasnić, 2021), iç denetçilerle ilgili bu alanda yapılmış bir araştırmaya rastlanmamıştır. Tükenmişlik sendromu bir meslek hastalığı olarak görülmesine rağmen birçok profesyonel meslekte olduğu gibi iç denetim mesleğinde konu hakkında bilgi eksikliği bulunmaktadır (Bernd ve Beuren, 2021).…”
Section: Hi̇potez Geli̇şti̇rme 1öz Yeterlilik Ve Mesleki Tükenmişlikunclassified
“…Ayrıca, yüksek öz yeterlilik inancını içinde barındıran iç denetçilerin, profesyonel yaşamdaki rolleri ile aile yaşamındaki rolleri birbirinden ayırarak, gerginlik temelli bir çatışmaya meydan vermeyecekleri de söylenebilir (Siu, 2013;Polatçı ve Akdoğan, 2014;Nina ve Fauziah, 2018;Kaplan, 2018;Badri ve Panatik, 2020;Akkuş, Najimudinova ve Gül, 2020;Parray, Shah ve Islam, 2022). Benzer bir şekilde sosyal bilişsel teoriye göre, iç denetçiler öz yeterlilik inançlarını kullanarak, mesleklerinde karşılaşmış oldukları psikolojik gerginliklerle ve stresle baş edebilirler ve mesleki tükenmişlik riskini azaltabilirler (Shoji vd., 2016;Arslan, 2019;Makara-Studzińska, Wajda ve Lizińczyk, 2020;Vidić, Đuranović ve Klasnić, 2021). Öte yandan, sosyal mübadele teorisine ve karşılıklılık normuna dayanarak, işletme yönetiminin, iç denetçilerin iş-yaşam dengesini sağlayabilmek için oluşturdukları insan kaynakları politika ve prosedürleri karşılığında iç denetçilerin mesleki tükenmişlik geliştirme eğilimine yönelmeyecekleri de ifade edilebilir (Martínez-León, Olmedo-Cifuentes ve Sanchez-Vidal, 2019).…”
Section: İş-yaşam Dengesinin Aracılık Rolüunclassified
See 1 more Smart Citation
“…In the classroom context, student misbehavior has been considered one of the greatest predictors of teacher burnout (e.g., Vidić et al, 2021; Yurt, 2022). In a study with Australian high school teachers, McCormick and Barnett (2011) found that the most salient stressor for burnout was teachers' perception of students' disruptive behaviors.…”
Section: Introductionmentioning
confidence: 99%